Rethinking (in)security in the European Union : the migration-identity-security nexus - Iov, Claudia Anamaria (Cambridge Scholars Publishing, 2020)
This book is the result of a series of studies devoted to assessing the consequences of migration from the perspective of the migration-identity-(in)security causality, with a specific focus on the Roma issue in France. It demonstrates that, in the context of the new European agenda on security, following the events of 9/11, immigrants, in general and the Roma, in particular, have found themselves trapped in a spiral of insecurity through which migration has been raised to the level of 'meta-problem' and they have become scapegoats. The book argues that these issues reflect a broader political.